Designing Usability and UX with UXUG-AP: An Observational Study and an Interview with Experts - Sousa, Aline de Oliveira; Valentim, Natasha Malveira Costa (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
Nowadays, there are several technologies (methods, techniques, among others) that help agile development teams to improve the Usability and User eXperience (UX) in their projects. Usability and UX are relevant aspects of software quality. In the literature, we find few technologies that help to improve the Usability and UX jointly at the beginning of agile process, mainly during the design phase, where to perform changes is easier and cheaper. Therefore, in our paper, we present the technique User Experience and Usability Guidelines for Agile Project (UXUG-AP), that aims to support the Usability and UX design. UXUG-AP is composed by categories, subcategories, and specific guidelines to help the prototyping process. We also present an observational study with agile professionals. The study was done to evaluate the ease of use, perceived usefulness and the intention to future use from UXUG-AP. The results show that is necessary requirements well defined in order to have a better use of the technique. In additional, we present an interview with experts in agile design which provide their opinions about UXUG-AP. The interview results show that some designers are used to evaluating their projects after development, instead of avoiding usability and UX issues at the beginning of process.